Reforming Welfare by Rewarding Work : One State's Successful Experiment - Hage, Dave (Book collections on Project MUSE., 2004)
In the late 1980s, Governor Rudy Perpich gathered a group of citizen experts to redesign Minnesota's welfare system, and a burst of innovation resulted in the groundbreaking and successful pilot Minnesota Family Investment Program (MFIP). Reforming Welfare by Rewarding Work intertwines MFIP's development with harrowing--and enlightening--firsthand accounts of three families' experiences on welfare, and asserts that a true antipoverty program is crucial--and achievable--in America.